Jornal 'Coração', o porta-voz da torcida corintiana: uma aventura na imprensa esportiva paulista (1976/1977) - Oliveira, Fábio Camargo Fleury de [UNESP] (2014)
This dissertation aims to reconstruct the history of 'Coração, a newspaper published during the 70s, in the capital of São Paulo state, by six young journalists from soccer written press, specially dedicted to the rooters of Sport Club Corinthians Paulista. The tabloid was released in the consumer market in October, 1976 and terminated its activies in December, 1977, with 58 editions, during 15 months of existence. The independent weekly publication, without any political or financial link to be black-and-white club, presented on its customary 16 pages a biased, simple, creative and direct language. Coração publicized all the facts and articulations involving the Corinthians universe, on and off field, on editorials, news, articles, photos and cartoons. This dissertation was composed using the newspaper as the object and source of itself and throughout the interview technique. The testimonies from the six founders of the tabloid were registered through audio recording and the research was conducted over the editions n. 1 to n. 10. The collected information intercross, forming a single text that recalls the journey of a peculiar journalistic product for the history of the Brazilian sports press